ANALISIS PENGARUH KUNJUNGAN WISATAWAN TERHADAP PERMINTAAN PRODUK LOKAL MASYARAKAT DESA ADAT BUALU - Fahmi Tanjung; I Made Sujana; Putu Ratna Windusara Putri; Ni Luh Wulani Parwati (Nusantara Hasana Journal, 2024)
Tourism development in Bali has significantly contributed to the growth of local economic activities, particularly in traditional villages that maintain cultural authenticity. Bualu Traditional Village, located in South Kuta District, Badung Regency, has experienced a substantial increase in tourist arrivals, creating opportunities for the development of local products such as handicrafts, culinary products, traditional fabrics, and cultural souvenirs. This study aims to analyze the influence of tourist visits on the demand for local products in Bualu Traditional Village. This research employed a quantitative descriptive approach. Data were collected through observations, interviews, questionnaires, and documentation involving local business actors and community members engaged in tourism-related activities. The data were analyzed using descriptive analysis and simple linear regression techniques. The results indicate that tourist visits have a positive and significant influence on the demand for local products. Increasing tourist arrivals contribute directly to higher sales volumes, business income, and the diversification of local products. The sustainability of local product demand is also supported by cultural preservation, community participation, and the development of creative economy initiatives. Therefore, strengthening local product competitiveness through innovation, digital marketing, and stakeholder collaboration is necessary to maximize the economic benefits of tourism.